STATUS AKREDITASI DAN KUALITAS SEKOLAH DI SEKOLAH DASAR NEGERI - Charisma Dewi Setiyaningsih (Universitas Negeri Malang, 2017)
Abstract: The aims of this research are to investigate: (1) the status school accreditation, (2) the school performance, (3) the relationship between accreditations standards and school performance. The research uses quantitative approach with correlational descriptive design. Participants of this study consist of 65 school including State Elementary School, in Batu Region that were selected through area sampling. Data were collected through survey questionares and analysed using descriptive analysis and Spearman Rank correlation. The findings are as follows: the majority of schools are accredited B, the school obtained higher performance of management operation, and there is a relations between status accreditations and school performance. keyword: status accreditation, school performance Abstrak: Penelitian ini bertujuan untuk mengetahui (1) tingkat akreditasi sekolah, (2) tingkat kulitas sekolah, dan (3) hubungan antara status akreditasi sekolah dengan kualitas sekolah. Penelitian ini menggunaan metode penelitian korelasional. Populasi dalam penelitian adalah 65 Sekolah Dasar (SD) Negeri di Kota Batu, dan menggunakan teknik area sampling. Selanjutnya teknik analisis yang digunakan adalah teknik analisis deskriptif dan teknik analisis korelasi Spearman Rank. Hasil penelitian menunjukkan bahwa, mayoritas SDN di Kota Batu terakreditasi B sebanyak 26%, kualitas sekolah berada dalam kategori tinggi, dan terdapat hubungan antara status akreditasi sekolah dengan kualitas sekolah. Kata kunci: status akreditasi sekolah, kualitas sekolah   DOI: https://doi.org/10.17977/um025v1i22017p138